Pengaruh Informasi dan Sifat Lupa Wajib Pajak terhadap Kepatuhan Wajib Pajak Orang Pribadi dalam Melaporkan SPT Tahunan PPh Pasal 21 - Whereson Siringoringo (President University Press, 2020)
Tax-based revenues are the backbone of the country's biggest source of funding this decade. Income tax as one of the central taxes that adhere to the Self Assessment System which requires compliance from the Taxpayer. The research is aim to determine the effect of Information and Forgetfulness Taxpayers on compliance with taxpayers in reporting the annual Income Tax Article 21. The research method used is quantitative with the study population is an Individual Taxpayer domiciled in Jabodetabek, using primary data obtained by using a questionnaire given to the research samples with the Non probability method, Accidental Sampling. The method of data analysis is multiple linear regression analysis. This study conclude that the Information variable has a positive significant effect on taxpayer compliance in reporting annual income tax returns, and the variable nature of forgetfulness does not have a negative significant effect on taxpayer compliance in reporting the annual income tax article 21, and simultaneously the information variable and the nature of forgetfulness have a significant effect to the compliance of taxpayers in reporting the annual income tax article 21.